2018
DOI: 10.1515/revneuro-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

A possible key role of vision in the development of schizophrenia

Abstract: Based on a brief overview of the various aspects of schizophrenia reported by numerous studies, here we hypothesize that schizophrenia may originate (and in part be performed) from visual areas. In other words, it seems that a normal visual system or at least an evanescent visual perception may be an essential prerequisite for the development of schizophrenia as well as of various types of hallucinations. Our study focuses on auditory and visual hallucinations, as they are the most prominent features of schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 259 publications
1
12
1
Order By: Relevance
“…All four groups of FUSCHAV patients demonstrated GMV reduction, primarily located in the temporal, occipital, frontal, and parietal lobes. These findings indicate that the primary auditory and visual cortex are impaired in FUSCHAV patients (Bernardin et al 2019;Csaszar et al 2019;Moseley et al 2018). The first episode of schizophrenic patients with congenital deficiency or serious brain damage is generally severe auditory and visual hallucinations.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…All four groups of FUSCHAV patients demonstrated GMV reduction, primarily located in the temporal, occipital, frontal, and parietal lobes. These findings indicate that the primary auditory and visual cortex are impaired in FUSCHAV patients (Bernardin et al 2019;Csaszar et al 2019;Moseley et al 2018). The first episode of schizophrenic patients with congenital deficiency or serious brain damage is generally severe auditory and visual hallucinations.…”
Section: Discussionmentioning
confidence: 76%
“…The patients in the current study were experiencing their first episode of schizophrenia and were unmedicated and therefore, these findings suggest that GMV reduction was present prior to the psychotic episode (Bordier et al 2018;Zmigrod et al 2016) and that there may be a brain-based pathology associated with the onset of AHs and VHs. Moreover, FUSCHAV patients demonstrated increased gFCD in the same brain regions showing GMV reduction suggesting that functional hyperactivity may compensation for structural impairment (Cao et al 2018;Collier et al 2014;Csaszar et al 2019;Kremlacek et al 2016;Xu et al 2016). Interestingly, FUSCHAV groups differed in GMV and gFCD alterations in some brain regions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the pilot study, all four FUSCHAV groups demonstrated GMV reductions, primarily in the temporal, occipital, frontal, and parietal lobes. These findings indicate that the primary auditory and visual cortexes are impaired in FUSCHAV patients (Bernardin et al, 2019; Csaszar, Kapocs, & Bokkon, 2019; Moseley, Mitrenga, Ellison, & Fernyhough, 2018). First‐episode schizophrenia patients with congenital deficiencies or serious brain damage generally have severe AHs and VHs.…”
Section: Discussionmentioning
confidence: 88%
“…Such impairment could be a biomarker of psychotic illness, as oxidative stress, NMDA receptor damage and deafferentation have all been noted to underlie both low-level sensory deficits and schizophrenia 19 . A few studies suggest an association between schizophrenia and reduced retinal fibre layer thickness 20,21 and visual processing abnormalities 22,23 . Visual problems are also a known side effect of antipsychotic medication and might therefore be an indirect result of psychosis.…”
Section: Introductionmentioning
confidence: 99%